Jezik (govor) v slovenskih gledališčih in jezikovna politika - Žavbi, Nina (Slavia Centralis, 2018)
In the article we focus on speech expression in theatre, predominantly on the needs of the users of the language (actors, language consultants, etc.) and the level of their language equipment. After an overview of the legislation and other legal documents (Public Use of the Slovene Language Act, Media Act, Exercising of the Public Interest in Culture Act and Resolution on the 2014-2017 National Programme for Culture) as well as after interpreting the results of empirical research we find that the current legislation from the field of language (speech) in theatre is adequate and that professional users would need several linguistic manuals (pronunciation guide, terminological dictionary) and a selection of guidelines about non-standard language forms.
Keywords: empirične raziskave; gledališče; govor; jezik; jezikovna politika; Language; pravorečni priročniki; theater